Formation Constants and Thermodrnamic Parameters of Mn2+, Co2+, Ni2+, Cu2+ and Zn2+ Chelates of Some 4-Formyloxime-2-Pyrazolin-5-ones. - SHAH, R.R.; BHOI, D.K.; KHARODAWALA, Mohammad J.; DABHI, H.R.; RAJ, D.S.; SOLANKI, K.S. (Asian Journal of Chemistry, 2010)
Stability constants and thermodynamic data of the chelates of 4-formyloxime-1,3-diphenyl-2-pyrazolin-5-one. 4-formyloxime-1( 2',4'-dinitrophenyl)-3-phenyl-2-pyrazolin-5-one and 4-formyloxime- 1-(2',4'-dinitrophenyl)-3-methyl-2-pyrazolin-5-one with Mn2+, Co2+, Ni2+, Cu2+ and Zn2+ have been determined of 25 and 35°C in 70 : 30 (v/v) dioxane-water media and 0.1 M KNO3, using Calvin-Bjerrum technique as applied by Irving and Rossotti. The stability data have been calculated using the different computational methods. The order of stability constants at both the temperatures is found to be Mn < Co < Ni < Cu > Zn for all systems. ΔG, ΔH and ΔS for the complexation have been derived.